2004
DOI: 10.1108/02621710410549585
|View full text |Cite
|
Sign up to set email alerts
|

Women managers: does positive action training make a difference?

Abstract: Despite long-standing legislation within the UK, women are still generally under-represented at managerial level within organisations. One method of making a difference to this situation is the provision of positive action training and this paper summarises the arguments for and against positive action. Also describes a case study of a positive action training initiative for women managers in local government and assesses its potential effectiveness as a means of breaking through the "glass ceiling". It explai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…These data were impossible to collect, as not every company reports them. However, in the general literature, several studies document the lack of representation of women and minorities on corporate boards and executive teams (Jackson, ; Anderson, ; Ryan and Haslam, ; Chicago United, ; Menendez, ; Alliance for Board Diversity, ). A cursory comparison of the diversity profile of our sample of corporations and the diversity profile of the senior management teams according to a survey of Fortune 500 and Fortune 100 companies confirms this disparity (Table )…”
Section: Resultsmentioning
confidence: 99%
“…These data were impossible to collect, as not every company reports them. However, in the general literature, several studies document the lack of representation of women and minorities on corporate boards and executive teams (Jackson, ; Anderson, ; Ryan and Haslam, ; Chicago United, ; Menendez, ; Alliance for Board Diversity, ). A cursory comparison of the diversity profile of our sample of corporations and the diversity profile of the senior management teams according to a survey of Fortune 500 and Fortune 100 companies confirms this disparity (Table )…”
Section: Resultsmentioning
confidence: 99%
“…Much of the functionalist writing and practice in the area of leadership development tends to treat the managerial subject as an abstract, asexual, non‐raced and somehow diversity‐neutral individual (Acosta 2004; Nkomo 1992). A more radical leadership development intervention, prompted by critical discourse, would aim to change the structures and cultures in the organization (Anderson 2004). This goes a lot further than just diversifying the people that do the work.…”
Section: Implications For Leadership Development Practice and Researchmentioning
confidence: 99%
“…Typically where an intervention was reviewed it was evaluated in the immediate to mid-term (e.g. Barnes et al 1998;Arksey 2003;Anderson 2004). Nevertheless, we did find encouragement in one study by Payne and Huffman (2005) which found that mentoring of USA army officers was positively related to affective commitment and negatively related to turnover behaviour.…”
Section: Introductionmentioning
confidence: 83%